Myocardial reporalization duration reflects autonomic nervous system activity in Takotsubo syndrome. (3rd May 2023) - Mantzouranis, E; Leontsinis, I; Sakalidis, A; Dalakouras, I; Dris, E; Drogkaris, S; Vlachakis, P; Liatakis, I; Manta, E; Antonopoulos, A; Fragkoulis, C; Konstantinidis, D; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Sympathetic overdrive has been proposed as a major precursor in Takotsubo syndrome (TTS) development. ECG changes in TTS often persist in time beyond the recovery of the cardiac systolic function and their prognostic significance remains unclear. Autonomic nervous system (ANS) fluctuations affect myocardial repolarization as well as the presence of myocardial oedema and active ischemia. Purpose: In this study we aimed to investigate the correlation between indices of ANS activity and the degree of QT interval prolongation during the course of TTS. Methods: We studied 30 patients (29 women, mean age: 66 ± 11 years, 17.2% history of diabetes mellitus) with a TTS diagnosis established after multimodality imaging evaluation, which included cardiac magnetic resonance imaging. Daily ECG recordings during the acute phase of the TTS were available for all patients. Both sympathetic and parasympathetic activity were evaluated with time and frequency domain indices of heart rate variability (HRV). Moreover, sympathetic tone was assessed by means of muscle sympathetic nerve activity (MSNA). All investigations were completed within 30 days of the index event. ANS indices were correlated with the maximum measured QTc interval of each patient during the acute phase of TTS. Results: Maximal QTc interval during the acute TTS phase exhibited a linear correlation with indices of sympathetic withdrawal. Specifically, QTc duration was positively correlated with rMSSD (r=430, p=0.036) and high frequency FFT (=0, 497, p=0, 016) whereas it was inversely associated with MSNA results measured in oscillations/100 heart beats (r=-573, p=0, 007). In a multivariate analysis model standardized for patients' age, left ventricular ejection fraction (synchronous with ECG measurements) and the usage of beta blocker medications the aforementioned results remained statistically significant (Table 2). Conclusion: In our population of TTS patients, increased parasympathetic activity and sympathetic withdrawal within the first month of the index event reflect increased repolarization duration during the acute phase of the syndrome.